A retrospective cohort study of 122 dogs treated for hypercortisolism: low-dose dexamethasone suppression test sensitivity and comparative outcomes in response to mitotane or trilostane - M.M. Marçal; S.F.M. Martins; C.R. Barbieri; T.B. Nogueira; Á.G. Pöppl (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Spontaneous hypercortisolism (HC), a prevalent endocrinopathy among elderly dogs, is mainly confirmed by the low dexamethasone dose suppression test (LDDST). However, its diagnostic sensitivity in Brazil is anecdotally reported low compared with published literature. Medical treatment with mitotane was the rule over decades in Brazil but has been progressively substituted by trilostane, an argued safer drug. This work evaluated the LDDST sensitivity and medical treatment efficacy of trilostane and mitotane in dogs treated for HC in Southern Brazil. The retrospective cohort study included 122 dogs treated with trilostane (58.2%) or mitotane (41.8%). Pituitary-dependent HC cases were overrepresented (81.96%). Treatment outcomes (P=0.61) and survival (P=0.16) were similar in response to mitotane or trilostane, with good clinical control achieved in 72.5% and 62.4% of dogs respectively. The LDDST sensitivity in this population was considered lower (77.8%) than reported in the literature with a cutoff of 1.4 µg/dL for 8-hour post-dexamethasone cortisol; however, a suggested 0.8µg/dL cutoff significantly (P=0.01) increased the test sensitivity to 85.2%. Mitotane should still be considered as a medical treatment option for canine HC. Individually reducing the LDDST cutoff in patients with well-documented clinical Cushing´s syndrome diagnosis could be worthwhile.